Understanding IBM eServer pSeries Performance and Sizing - Gfroerer, Diana; Trickett, Nigel; Nakagawa, Tatsuhiko; Mani, Ravi (IBM redbooks., 2001)
This IBM Redbooks publication is an update to the successful first edition of Understanding IBM RS/6000 Performance and Sizing, SG24-4810 that was published in 1997. It gives a broad overview of IBM RS/6000 and IBM eServer pSeries performance and sizing. Contained in this book is a close-up, performance related view of the different hardware architectures IBM offers in its RS/6000 and eServer pSeries systems, including system, processor, memory, storage, and network architectures. One chapter is dedicated to general sizing rules for a number of environments such as database sizing, IBM HTTP server sizing, Net.Commerce sizing, and Lotus Domino sizing. The reader will also find a description of the industry benchmarks that are performed on IBM systems as well as an overview of AIX performance tools. This book is intended to be a handbook for anyone who wants to gain a deeper understanding of IBM RS/6000 and IBM eServer pSeries architectures from a performance perspective.